ANALISIS FAKTOR PENYEBAB PERNIKAHAN DINI DAN DAMPAKNYA BAGI PELAKUNYA - Mubasyaroh Mubasyaroh (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
This article focuses on factors and impacts of child marriage from the perspective of sociology and psychology. Using descriptive qualitative analysis, this article attempts to address the problem in-deep. The Article 7 of Law No 1 Year 1974 states that the minimum age for marriage is 19 for male and 16 for female, thus child marriage is basically illegal. Child marriage is mostly bring negative impact for female such as premature aging syndrome due to her role as wife and mother.